Religious/spiritual coping in informal caregivers of children with cleft lip and/or dysphagic palate - Francely Tineli Farinha; Gesiane Cristina Bom; Maila Meryellen Ferreira Garcia Manso; Priscila Capelato Prado; Claudia Regina Matiole; Armando dos Santos Trettene (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to identify the use of religious/spiritual coping in informal caregivers of children with cleft lip and/or palate, dysphagic, powered exclusively by probe. Methods: descriptive and cross-sectional study, including 30 informal caregivers. For data collection, a Sociodemographic Questionnaire and the Brief Religious/Spiritual Coping Scale were used. For statistical analysis, ANOVA, Student's t and Spearman's correlation tests were used, with a significance level of 5%. Results: the use of religious/spiritual coping was high among participants (mean=3.71), with a predominance of positive (mean=3.30) compared to negative (mean=1.88). It was evident that the greater the reported importance of religiosity/spirituality in the participants' lives, the greater the positive coping (p=0.001). Conclusions: informal caregivers used positive religious/spiritual coping as a way of coping with care demands related to the child's health condition. These findings point to the importance of including spirituality/religiosity as health indicators.